Exceptional Paper—A Theory of the U.S. Treasury Market Equilibrium - Barry, John Y.; Ayres, Herbert F. (Management Science, 1980)
Above maturities of six months to a year, the equilibrium yield to maturity for government securities consists of two statistically independent components. The first, the so-called “consol yield,” is the same for every maturity. The change in the consol yield has the same impact on yield for every maturity and the mere knowledge of its sign dominates opportunities for trading profits. However the expected change in the consol yield and all other yields is zero. The absolute value of the second component, “spread,” declines exponentially as maturity lengthens, despite variations in both its sign and magnitude. Examination of 20 years of evidence suggests that any departures of actual yields from the exponential model are only temporary. The authors argue that their model satisfies the “no free lunch” property of efficient securities markets: There is no strategy that will increase expected total return in the absence of forecasting skill. They also argue that their model is consistent with the trading behavior of professional bond managers, who judge the yield on a bond by making “butterfly comparisons” with yields on bonds of greater and lesser maturity, disregarding investment horizon. Finally, they present the full stochastic model of the equilibrium yields, and test it economically and statistically. It is in conflict with many “modern” financial theories, but it provides a description of what must be done to beat a buy and hold strategy without which no paper on any market is complete.